The Influence of Organizational Culture, Work Team and Competence on The Performance of Private Personnel of Rifle Company C, Battalion 461, Rapid Movement Force Command - Andri, Fadli; Yanthy Yosepha, Sri; Sukendar, Tateng; Widodo, Sri (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
This study aims to analyze the influence of organizational culture, work team, and competence on the performance of the enlisted personnel of Rifle Company C Battalion 461 Kopasgat. This study uses a quantitative approach, survey method and path analysis. The population with saturated sampling technique obtained 52 respondents. Data were analyzed using Excel and SPSS 25 software. The results of the study indicate that: Organizational culture has a direct positive and significant effect on competence of 0.334; Work team has a direct positive and significant effect on competence of 0.663; Organizational culture has a direct positive and significant effect on performance of 0.501; Work team has a direct positive and significant effect on performance of 0.418; Competence has a direct positive and significant effect on the performance of enlisted personnel of Rifle Company C Battalion 461 Kopasgat of 0.243.